Association of environmental enteropathy with prediabetes and diabetes: A cross-sectional study among Tanzanian adults - George PrayGod; Belinda Kweka; Evangelista Malindisa; Andrea M. Rehman; Ruth Frikke-Schmidt; Christina Christoffersen; Rikke Krogh-Madsen; Daniel Faurholt-Jepsen; Henrik Friis; Paul Kelly; Suzanne Filteau (PLoS ONE, 2025)
Objectives Environmental enteropathy (EE) may increase the risk of diabetes, but data are limited. We assessed the role of EE on markers of glucose metabolism. Methods Cross-sectional study among Tanzanian adults assessing EE and diabetes was conducted between 2019 and 2021. Data on demography, body mass index (BMI), Human immunodeficiency virus (HIV), EE (i.e., fecal myeloperoxidase, lipopolysaccharide binding protein, and markers of intestinal permeability and absorption capacity), glucose and insulin were collected. Data reduction using principal components analysis produced two components: sugar uptake and inflammatory EE. Tertiles were used to define EE severity as: lower, middle, and upper. The main outcome, combined prediabetes and diabetes, was defined as 2-hour oral glucose tolerance test (OGTT) glucose ≥7.8 mmol/L. Lower homeostatic model assessment (HOMA)-β and insulinogenic index, higher HOMA-insulin resistance (HOMA-IR), and lower Matsuda index were secondary outcomes. Logistic regression assessed the associations and HIV and BMI groups were tested as effect modifiers. Results A total of 612 participants were included. The mean (±SD) age was 42.0 (±11.6) years and 57.2% (350) were females. Eighty (13%) were underweight, 367 (60%) normal weight, 165 (27%) overweight, and 357 (58%) were HIV-infected. We found no overall association of EE on the main outcome, but BMI and HIV modified the associations. Compared to lower tertile of sugar uptake EE, the upper tertile was associated with marginally significant higher odds of prediabetes and diabetes (OR=2.1 (95% CI: 0.9, 4.9; P = 0.06)) and marginally significant higher HOMA-IR (OR=2.6 (1.0, 6.8; P = 0.06)) among overweight and obese participants. Similarly, compared to the lower tertile, the upper tertile of inflammatory EE was associated with higher odds of prediabetes and diabetes (OR=2.1 (1.1, 4.1; P = 0.03)) among HIV-uninfected participants, whereas among HIV-infected participants those in the middle tertile compared to those in the lower tertile had higher odds of lower Matsuda index (OR=2.3 (1.1, 4.7; P = 0.03)). Conclusions EE may increase the risk of prediabetes and diabetes among those who are overweight and in individuals who are not HIV-infected. Longitudinal studies on the role of EE on diabetes are needed to confirm these results to provide the basis for developing and testing novel interventions to combat diabetes in Africa.